Negative Impoliteness in “Ellen DeGeneres” Talk Show: Pragmatic Approach - Wendy Wendy; Ambalegin Ambalegin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research is using pragmatic study to observe the types of negative impoliteness based on the talk show "Ellen DeGeneres" hosted by Ellen DeGeneres. The function of this research was to find out the types of negative impoliteness that occurred in the talk show. Then, the utterances were discovered and collected by taking the theory of Culpeper (2011) to the data source. The object for this research was the negative impoliteness. The data source uttered by both speaker and hearer from the talk show "Ellen DeGeneres".  To provide the research aftermath, the research design used was the descriptive qualitative. The method of collecting data technique was using the nonparticipator observation Sugiyono (2010). Why technic of collecting data in this research as follow. Firstly, the researchers watched the interview on the "Ellen DeGeneres" talk show. Secondly, the researchers read the transcript and search the context for analysis. Finally, the researchers found out all the issues related to the impoliteness from the negative politeness in the "Ellen DeGeneres" talk show. The method of analysis the data was categorization proposed by Sugiyono (2010) method was completed by analyzing "Ellen DeGeneres" talk show. There were 20 negative impoliteness utterances uttered by both speaker and hearer in the talk show and the researchers analyzed it all. The types of negative impoliteness uttered by both speaker and hearer were 5 affective, 3 coercive, and 12 entertaining.